2009
DOI: 10.1007/s00431-009-1009-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased type 3 iodothyronine deiodinase activity in a regrown hepatic hemangioma with consumptive hypothyroidism

Abstract: It is important to identify infantile hepatic hemangioma in patients with hypothyroidism refractory to hormone replacement therapy, who have low free triiodothyronine despite high thyrotropin and normal free thyroxine levels, and long-term follow-up will be needed for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…In a recent case report, the expression of D3 activity in the resected tumour was found to be significantly higher than the mean of placental tissues of four subjects. 4 The tumoral D3 expression in these vascular lesions together with the disappearance of hypothyroidism after liver transplantation or HHE involution support the concept that this endocrinopathy is due to excessive degradation of thyroid hormones. 3,4 The rate of T4 degradation is a product of the enzyme activity and the mass of the HHE; hence the large variations in values of TSH and fT4 reported in the previous cases.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In a recent case report, the expression of D3 activity in the resected tumour was found to be significantly higher than the mean of placental tissues of four subjects. 4 The tumoral D3 expression in these vascular lesions together with the disappearance of hypothyroidism after liver transplantation or HHE involution support the concept that this endocrinopathy is due to excessive degradation of thyroid hormones. 3,4 The rate of T4 degradation is a product of the enzyme activity and the mass of the HHE; hence the large variations in values of TSH and fT4 reported in the previous cases.…”
Section: Discussionmentioning
confidence: 60%
“…4 The tumoral D3 expression in these vascular lesions together with the disappearance of hypothyroidism after liver transplantation or HHE involution support the concept that this endocrinopathy is due to excessive degradation of thyroid hormones. 3,4 The rate of T4 degradation is a product of the enzyme activity and the mass of the HHE; hence the large variations in values of TSH and fT4 reported in the previous cases. It has been reported that the most rapid rate of T4 degradation is associated with the proliferative phase of HHE.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…If anti-TPO antibodies are absent, less common etiologies of primary hypothyroidism should be considered for example transient hypothyroidism due to postsubacute thyroiditis, hypothyroidism related to external irradiation (69) and consumptive hypothyroidism due to the inactivation of thyroid hormone by the paraneoplastic expression of type III iodothyronine deiodinase, mostly in vascular tumors (70). The typical patient with hypothyroidism secondary to HT has an elevated TSH, a low fT4, and positive anti-TPO antibodies.…”
Section: Diagnosismentioning
confidence: 99%